2021
DOI: 10.1186/s12885-021-08744-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative morbidity and quality of life between totally laparoscopic total gastrectomy and laparoscopy-assisted total gastrectomy: a propensity-score matched analysis

Abstract: Background This study aimed to evaluate the surgical outcome and quality of life (QoL) of totally laparoscopic total gastrectomy (TLTG) compared with laparoscopy-assisted total gastrectomy (LATG) in patients with clinical stage I gastric cancer. Methods From 2012 to 2018, EGC patients who underwent TLTG (n = 223), including the first case with intracorporeal hemi-double stapling, were matched to those who underwent LATG (n = 114) with extracorporea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…IEJ-related complications are an important topic in terms of using digestive reconstruction methods in TLTG. Previous studies have revealed that the rate of postoperative IEJ-related complications ranged from 0% to 11.7% [ 27 29 ]. The majority of the previous comparisons of IEJ-related complications between LS and CS approaches involved retrospective studies with small sample sizes; thus, the results are inconsistent and even contradictory [ 5 , 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…IEJ-related complications are an important topic in terms of using digestive reconstruction methods in TLTG. Previous studies have revealed that the rate of postoperative IEJ-related complications ranged from 0% to 11.7% [ 27 29 ]. The majority of the previous comparisons of IEJ-related complications between LS and CS approaches involved retrospective studies with small sample sizes; thus, the results are inconsistent and even contradictory [ 5 , 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether TLG can improve the QOL of patients after surgery is still controversial. Park et al [ 7 ] compared QOL within 1 year after TLTG and LATG, and the results indicated that postoperative dysphagia, pain, eating and odynophagia were significantly improved in the TLTG group compared with the LATG group[ 7 ]. Wei et al [ 26 ] used circular anastomosis and found that postoperative constipation, dysphagia and anastomotic complications were significantly improved in TLTG group patients compared with LATG group patients[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…With continuous improvements in surgeons’ skills and improvements in intracorporeal staplers, totally laparoscopic gastrectomy (TLG) with complete intracorporeal anastomosis has become a research hotspot. Previous studies have shown that compared with laparoscopic assisted gastrectomy (LAG) or open gastrectomy, TLG requires a smaller incision, induces less postoperative pain and improves postoperative quality of life (QOL)[ 7 , 8 ]. These advantages are also shown in patients who have received the neoadjuvant chemotherapy[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, TG may achieve adequate resection margins and radical lymph node dissection; however, it is accompanied by poor postoperative nutritional status, characterized by anemia and weight loss 1,3,4 . PG may improve the postsurgical nutritional status and quality of life (QOL) of patients because of the preserved remnant stomach, which stores food and promotes the absorption of iron, vitamin B12, and other nutrients 5,6 . However, in addition to the risk of remnant cancer, PG raises concerns that the presence of a residual stomach may reduce QOL because of acid reflux esophagitis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 PG may improve the postsurgical nutritional status and quality of life (QOL) of patients because of the preserved remnant stomach, which stores food and promotes the absorption of iron, vitamin B12, and other nutrients. 5,6 However, in addition to the risk of remnant cancer, PG raises concerns that the presence of a residual stomach may reduce QOL because of acid reflux esophagitis. 7 Thus, the clear advantages gained by improving postoperative QOL must be demonstrated to qualify PG as standard procedure.…”
mentioning
confidence: 99%